KONSTRUKSI MODEL PEMBINAAN SANTRI DI PONDOK PESANTREN HIDAYATUL MUBTADIIN PENARUKAN KEPANJEN - Syarfil Anam, Didik; Mudhofar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Student development is a fundamental component of Islamic boarding school education as it plays a vital role in shaping students` character, religious knowledge, and moral values. However, the student development system at Pondok Pesantren Hidayatul Mubtadiin, Penarukan Kepanjen, has not yet been supported by structured guidelines, competency standards, comprehensive monitoring and evaluation, or a sustainable development framework. This study aims to describe the implementation of student development, identify its supporting and inhibiting factors, and construct a student development model that meets the needs of the boarding school. A qualitative approach with a case study design was employed. Data were collected through observation, semi-structured interviews, and documentation involving the caregiver, administrators, teachers, students, and parents selected using purposive sampling. Data were analyzed using the Miles, Huberman, and Saldaña interactive model, while data validity was ensured through source and technique triangulation. The findings reveal that student development has been implemented through classical Islamic book learning, religious habituation, and teacher mentoring. Nevertheless, its implementation remains unstructured due to the absence of standardized guidelines, competency standards, comprehensive evaluation, and a clear continuation pathway after the Wustha level. Based on the needs analysis, this study constructs the Ri`ayah Model, consisting of planning, implementation, monitoring, evaluation, and sustainability components. The model is expected to serve as a practical guideline for establishing a more systematic, integrated, and sustainable student development system in Islamic boarding schools.